(untitled) (Revista Electrónica REDINE, 2020)
We live in a constant reflective process about the situations and events that arise in our daily work. Realities that go from the simplest to the interwoven. Just as the spherical white or reddish layers of a plant called "onion" are formed, one on top of the other, which seem to protect its central nucleus. In a similar way, our experiences could be perceived, which are subtly fusing to form a dense mantle that allows us to respond to entelechies throughout our existence. As we do today in the face of an intricate global environment as a result of the COVID19 pandemic, which surprised us in the midst of the current controversies in each of the countries of the globe. The reason that leads me to write this essay that seeks to share certain concerns subject to the new rules that we must adopt and the attitude we must assume. That is why I offer you some alternatives to adapt and see an opportunity in the face of adversity. With this writing it is intended to have a creative vision of the use of the mask in classrooms, product of the deliberations arising from COVID19.